Genetic-clinical profile of subjects with apparently sporadic extra-adrenal paragangliomas - Ramundo, Valeria; Ercolino, Tonino; Faggiano, Antongiulio; Giachè, Valentino; Ragghianti, Benedetta; Rapizzi, Elena; Colao, Annamaria A.; Mannelli, Massimo (Frontiers in Endocrinology, 2012)
Background: Mutations in the genes encoding B, C and D subunits of the succinate dehydrogenase (SDH) are involved in the pathogenesis of familial paraganglioma (PGL) syndrome. Many subjects with apparently sporadic extra-adrenal paragangliomas are found to be carrier for SDH mutation. Objective: Here we describe 4 subjects with apparently sporadic extra-adrenal paragangliomas with newly identified mutations in the SDH subunit B and the related clinical phenotype. Methods: Gene sequencing was performed to search for mutations in the SDHB (all exons), SDHC (all exons) and SDHD (all exons) genes as well as VHL ( all exons) and RET (10, 11, 13, 14, 15, 16 exons) genes in all four index cases. A complete clinical, biochemical and instrumental work-up was performed. Results: Three subjects were found to be affected with a nonsense SDHB germ-line mutation (Q30X, Y61X and W201X, respectively). These mutations are predicted to encode for a truncated SDHB protein. The fourth subject presented a S195del frameshift mutation, causing a deletion of the codon AGC, encoding for a serine. Clinical presentation and course of each patient is described. Conclusions: Extra-adrenal paragangliomas, localized in the sympathetic ganglia (in the posterior thorax or in the abdomen), are very often SDHB-inherited form rather than sporadic tumor. Our data confirm the importance of genetic screening in patients affected with paragangliomas and enlarge the list of mutations responsible for the presence of these tumors.